Dataset for: Overflow-Aware Recycling Bin Location with Random Utilities: A Case Study of the Commune of Estación Central, Chile - JARA-MORONI, PEDRO; MENDEZ-VOGEL, GONZALO; Marianov, Vladimir; Zamorano, Jorge; Dávila-Gálvez, Sebastián (Usach, 2025)
Project title: Overflow-Aware Recycling Bin Location with Random Utilities: A Case Study of the Commune of Estación Central, Chile Authors: Méndez-Vogel, G., Dávila-Gálvez, S., Jara-Moroni, P., and Zamorano, J. --------------------------------------------- Description: This repository contains the datasets used in the computational experiments presented in the paper “Overflow-Aware Recycling Bin Location with Random Utilities: A Case Study of the Commune of Estación Central, Chile.” All model parameters, behavioral assumptions, and experimental settings are described in detail in the paper. The data files provided here correspond to the spatial inputs used to reproduce the optimization and simulation results. --------------------------------------------- Files included: 1. Glass_generation_points.txt This file contains the set of demand points representing locations where glass waste is generated. Each row corresponds to a demand point with the following tab-separated columns: latitude Latitude coordinate of the demand point longitude Longitude coordinate of the demand point glass generated (kg) Estimated weekly quantity of glass generated at the location, in kilograms These points are used to model the spatial distribution of glass waste generation across the study area (Estación Central, Chile). --------------------------------------------- 2. Candidates.txt This file contains the candidate locations for installing or reallocating glass recycling bins. Each row corresponds to a potential facility site, with the following tab-separated columns: latitude Latitude coordinate of the candidate site longitude Longitude coordinate of the candidate site These coordinates define the discrete set of potential bin locations considered by the optimization model. --------------------------------------------- All settings, including user behavior modeling (random utilities), overflow penalties, bin capacities, and spatial parameters, are fully documented in the paper.
Keywords: Other; Matemáticas; Ingeniería Ambiental